Trends in worker displacement penalties in Japan: 1991 - 2005 - Michael Bognanno; Ryo Kambayashi (Institute for the Study of Labor (IZA), 2007)
We examine the period from 1991 to 2005 to document the effects of a changing Japanese labor market on trends in the cost of job change. During this period, job change penalties and the extent to which they were age-related grew. Evidence is also found of a diminishing specificity in human capital (in industry, occupation and firm size) for job changers in the Japanese labor market. As might be expected, older workers and workers leaving the largest firms suffered the largest wage losses from job change. Older workers were also harmed more by involuntary job separations. In percentage terms, young females have larger wage losses than young males but older females have smaller losses than older males. This pattern is masked in considering only the overall effect of gender on the cost of job change.
Keywords: 330; Arbeitsmobilität; Lohn; Japan